Governance of the Smart Mobility Transition - Marsden, Greg (Emerald Publishing Limited, 2018)
The transition towards 'smarter' autonomous transport systems calls for a rethink in how transport is governed/who governs it, to ensure a step-change to a more sustainable future. This book critically reflects on these governance challenges analysing the role of the state; the new actors and discourses; and the implications for state capacity
Description based on publisher supplied metadata and other sources